New species of Microchirita (Gesneriaceae) from Thailand - Middleton, David J.; Triboun, Pramote (Thai Forest Bulletin (Botany), 2013)
Five new species of Microchirita are described: Microchirita purpurea D.J.Middleton & Triboun, Microchirita karaketii D.J.Middleton & Triboun, Microchirita suddeei D.J.Middleton & Triboun, Microchirita albiflora D.J.Middleton & Triboun and Microchirita woodii D.J.Middleton & Triboun.